Transcription activation is enhanced by multivalent interactions independent of phase separation - Trojanowski, Jorge; Frank, Lukas; Rademacher, Anne; Mücke, Norbert; Grigaitis, Pranas; Rippe, Karsten (Molecular cell, 2022)
Transcription factors (TFs) consist of a DNA-binding domain and an activation domain (AD) that are frequently considered to be independent and exchangeable modules. However, recent studies report that the physicochemical properties of the AD can control TF assembly at chromatin by driving phase separation into transcriptional condensates. Here, we dissected transcription activation by comparing different synthetic TFs at a reporter gene array with real-time single-cell fluorescence microscopy. In these experiments, binding site occupancy, residence time, and coactivator recruitment in relation to multivalent TF interactions were compared. While phase separation propensity and activation strength of the AD were linked, the actual formation of liquid-like TF droplets had a neutral or inhibitory effect on transcription activation. We conclude that multivalent AD-mediated interactions enhance the transcription activation capacity of a TF by increasing its residence time in the chromatin-bound state and facilitating the recruitment of coactivators independent of phase separation.
Gesehen am 13.07.2022